2013
DOI: 10.1371/journal.pone.0060285
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Subdomains in the Resorbing Surface of Osteoclasts

Abstract: We employed a novel technique to inspect the substrate-apposed surface of activated osteoclasts, the cells that resorb bone, in the scanning electron microscope. The surface revealed unexpected complexity. At the periphery of the cells were circles and crescents of individual or confluent nodules. These corresponded to the podosomes and actin rings that form a ‘sealing zone’, encircling the resorptive hemivacuole into which protons and enzymes are secreted. Inside these rings and crescents the osteoclast surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Recently, Szewczyk et al reported that the distribution of F-actin and lysosomal proteins in OCLs is very similar on bone slice and vitronectin-coated glass coverslips27. On vitronectin, ashen OCLs displayed more irregular shape of F-actin formation than wild-type OCLs (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Recently, Szewczyk et al reported that the distribution of F-actin and lysosomal proteins in OCLs is very similar on bone slice and vitronectin-coated glass coverslips27. On vitronectin, ashen OCLs displayed more irregular shape of F-actin formation than wild-type OCLs (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…There is a growing body of evidence about the unexpected heterogeneity of podosomes within the SZ of the OCs (Anderegg et al, ; Batsir et al, ; Geblinger, Geiger, & Addadi, ; Saltel et al, ; Szewczyk, Fuller, & Chambers, ). In addition, Joosten, Willemse, Fransen, Cambi, and van den Dries () showed that podosome clusters in dendritic cells comprise many different types based on types of actin filaments and the immunolocalization of vinculin and zyxin.…”
Section: Discussionmentioning
confidence: 99%
“…5 ) 48 , Arp2/3 ( Supplementary Fig. S5 ) 25 49 , dynamin ( Fig. 6 ) 23 50 and membranous structures 15 at RP at AP-structures to indicate active on-going resorption ( Supplementary Figs S3–S4 ).…”
Section: Discussionmentioning
confidence: 99%